Letter : International Brigade Association - Child, H. E.
035-0043-001 SOUTHAMPTON TRADES COUNCIL 35 LYTHAM ROAD, BITTERNE PARK, SOUTHAMPTON SECRETARY H.E. CHILD TELEPHONE SOUTHAMPTON 75982 31st October, 1950. Mr. R. Boyfield, Secretary, Organisation Department, Trades Union Congress, Transport House, Smith Square, London. S.W.1. Dear Mr. Boyfield, International Brigade Association. In response to a circular letter received from the International Brigade Association in connection with the deportations of Spanish Republicans from France, my Council decided to send a protest to the French Embassy. The circular also requested financial aid to further the Association's campaign to assist these Spanish anti-Fascists, and I am asked to inquire if the International Brigade Association is an organisation to which a donation could he made from Trades Council funds. Yours sincerely, H.E. Child, Secretary. 292/946/35/43